Dynamics of helical domain wall in cylindrical nanowires - Wong, Shawn De Wei (2015)
We report on the dynamics of helical domain wall (DW) in 350-nm-diameter cylindrical NiFe nanowires. Our micromagnetic simulations findings show that a minimum current density is needed to overcome the intrinsic pinning to drive the helical DW. At low current density, the helical DW undergoes a rotation during its propagation. At high current density, this rotation ceases while the DW propagates at an increased velocity. However, the helical DW experiences a velocity barrier which results in the decrease of the DW mobility. The current-induced motion of the helical DW maintains a stable DW profile, without any sign of structural breakdown, even at relatively high applied current. Anisotropic magnetoresistance (AMR) measurements were used to observe and study the generation and driving of the helical DW. The magnetization reversal process in single NiFe cylindrical nanowire has been investigated by the MR effect with the angle between the applied external magnetic field and the nanowire long axis. For field-induced dynamics of the helical DW, the AMR showed an abrupt transition at the switching field. For current-induced dynamics, the injected pulsed current has succeeded in driving the helical DW, in the absence of a magnetic field. In addition, we found that the minimum current density of a greater magnitude is needed to overcome the intrinsic pinning to drive the helical DW.